DBiochemical effect of Ginko biloba extract on carbohydrate metabolism in (induced type two) diabetic rats - Omayma A.R.; Zaid A.; Ali H.A.; EL-Regaily A.F.Y. (Medicamentul Veterinar)
Ginkgo biloba extract (EGb 761) has been used in traditional Chinese medicine for 5000 years that possesses various biological activities and has been shown to be useful in diabetes treatment. This study was carried out on 120, 12-14 weeks old male rats and weighted 150-200 gm. Rats were classified into two main large experiments. Experiment 1: Non-diabetic rats Included 40 of normal male rats were divided into two groups each one comprises 20 rats kept in separate metal cages and classified as follows: Group 1: Non-diabetic rats were administered with 0.2 ml of normal saline only (control group).Group 2:Non-diabetic rats were received (GBE) (120 mg/kg), given orally by stomach tube and daily for 6 weeks.Experiment 2: Diabetic rats "STZ group" Included 80 male diabetic rats were divided into four groups each one comprises 20 rats kept in a separate metal cages and classified as follows: Group 1: Diabetic rats were administered with 0.2 ml of normal saline only (diabetic control group).Group 2: Diabetic rats were received (GBE) (120 mg/kg), given orally by stomach tube and daily for 6 weeks. Group 3: Diabetic rats were received glimepiride (20mg/kg), given orally by stomach tube and daily for 6 weeks. Group 4: Diabetic rats received glimepiride in combination with (GBE), given orally by stomach tube and daily (1:1) for 6 weeks. Blood samples were collected from all animals groups after 3 and 6 weeks from treatment. Serum were separated and processed directly for (glucose, Lactate, total cholesterol, triacylglycerol, Minerals (Na+, K+, Ca++), L-MDA) concentration-(insulin, Glucagon, Testosterone) levels- (AST and ALT) activities were the parameters of biochemical interest investigated. The obtained results revealed that, a significant increase in serum glucose, total cholesterol, triacylglycerol, ALT, AST, L-MDA concentration. On contrary, a significant decrease in serum lactate, insulin, glucagon, testosterone, Na+, K+, Ca++ levels were observed in streptozotocin-induced diabetic rats allover the periods of the experiments when compared with normal control group. The results of this study indicated that (GBE) has potential benefits in diabetes treatment.